Rural transformation and sustainable livelihood approaches under regional environmental policies: Evidence from two villages in the Yangtze River Delta metropolitan region, China - Yan, Simin; Chen, Chen (Sustainable development, 2025)
Hasty and often uncontrolled urbanization and industrialization in metropolitan regions have pressured fragile rural ecosystems and large-scale rural livelihoods in China. Through in-depth observation and face-to-face interviews with key insiders in the villages of China's largest metropolitan region, the Yangtze River Delta, findings show that environmental policies in this region have profoundly influenced the local institutional processes and rural transformation. Through the lens of a modified sustainable livelihoods approach (MSLA), two institutional processes in formulating livelihoods strategies have stood out from case villages—state sponsorship exemplified by Yu village and grassroots entrepreneurship exemplified by Daxi village—and achieved sustainable livelihood outcomes in both collective level and household level. In particular, state-sponsored development in Yu village was strongly supported by local leadership and trust between local cadres and villagers. In contrast, grassroots entrepreneurial development in Daxi village emphasized rural entrepreneurs' self-learning and self-governance capacities. As such, we argue that making sustainable livelihood strategies is not a unidirectional process like top-down or bottom-up, albeit multifaceted alternatives intertwined with dynamic institutional processes for collectives and households in rural areas. Ultimately, we call for more vivid and in-depth case studies to nuance regional geography and its contextual attributes in further sustainable livelihood research in rural areas.
Erstveröffentlicht: 09. Oktober 2024
Gesehen am 10.04.2025